PENGARUH GAYA HIDUP DAN TEKNOLOGI TERHADAP SIKAP DAN KEPUTUSAN PENGGUNAAN KARTU KREDIT PADA BANK NEGARA INDONESIA CABANG KOTA PEKANBARU - Nurfikri, Abdul; Jahrizal, Jahrizal (Jurnal Tepak Manajemen Bisnis, 2019)
This study aims to measure the influence of lifestyle and technology onattitudes and decisions on the use of credit cards at the Pekanbaru state bankpekanbaru. The population in this study is the customer of the Pekanbaru branchof the Negara Indonesia bank by determining the number of samples using theSlovin formula, and obtained a sample of 100 people from a total population of243,770 people, using sample probability using the cluster random samplingmethod. Data analysis using Partial Keast Square with the help of SmartPLSversion 3.0.The results of calculations that have been done that the magnitude of thecoefficient of influence of variable X1 (Lifestyle) on the Y2 variable (use decision)is 0.362 with a t-statistic value of 2.959 greater than the t-table value of 1.290.While the magnitude of the effect coefficient of variable X2 (Technology) on thevariable Y2 (Use Decision) obtained is 0.793 with a t-statistic value of 5.514greater than the t-table value of 1.290. The magnitude of the coefficient ofinfluence of variable Y1 (attitude) on the variable Y2 (Use Decision) obtained is0.304 with a t-statistic value of 1.587 greater than the t-table value of 1.290.The results of the study that lifestyle is very influential on the use decisionsin the statement of interest in using a credit card and adding to the pride of pridein using credit cards and the development of technology is very influential on theuse decision to help pay more effective and efficient and safe in making payments.